KOORDINASI PELAKSANAAN PEMBIAYAAN PROGRAM KESEHATAN IBU DAN ANAK DI KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT TAHUN 2011 - Tudiono, Lalu Najmul Erpan, Laksono Trisnantoro, (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: Health financing provided by the governmentgreatly helps the implementation of health system in the decentralizedera. General Allocation Fund and Local Revenueand Expenditure Budget are apparently inadequate to financehealth service. Some efforts have been made to finance healthservice such as Community Health Insurance (Jamkesmas),Childbirth Insurance (Jampersal), and Health Operational Fund(Bantuan Operasional Kesehatan/BOK). These are meant toachieve Millennium Development Goals in 2015. The practiceof coordination from planning to implementation and stakeholdersâcommitment can affect the process of maternal and childhealth service. Coordination is definitely needed to run theprogram policy and prevent the overlapping financing in orderthat the objective of the program can be achieved.Objective: To evaluate coordination of planning, implementationand stakeholdersâ commitment in relation to maternal andchild health (MCH) service in Lombok Tengah District.Method: This was a descriptive-analytical study with a qualitativeapproach and a case-study design. Samples were takenpurposively. The data were obtained through in-depth interview,observation and documentation analysis.Result: The planning coordination of MCH health financinghad not been optimal, even despite the involvement of crosssector and program. However, the organizations of healthprofessionals were not involved in program planning. The coordinationof health financing implementation had not been optimalas well. Even though there was no overlapping financingfrom some different sources, in the policy implementation therewas cost sharing for referral and drugs. Private sectors werenot involved in the implementation of Jampersal. Stakeholdersâcommitment was relatively optimum as reflected from the policyand action in health development acceleration particularly MCH.The process of MCH service at both primary and secondarylevel could run well.Conclusion: Coordination of MCH financing implementation inLombok Tengah District through BOK, Jampersal, Jamkesmas,Community Empowerment National Program of Healthy andSmart Generation and Local Revenue and Expenditure Budgethad not been optimal; therefore, it needed to be improved toeliminate cost sharing. Professional organizations and privatehealth providers were not yet involved in the program planningand implementation.Keywords: coordination, stakeholdersâ commitment, healthfinancing, maternal and child health, program evaluation